APLIKASI PERPUSTAKAAN DIGITAL PADA FAKULTAS TEKNOLOGI INDUSTRI UPN “VETERAN” YOGYAKARTA - Wisnu Tri Nugroho (Jurusan Teknik Informatika, 2013)
UPN Veteran Yogyakarta central library is already implementing information systems inlibraries or short bias CYPRUS. However, the library information system only to simplify theprocess of borrowing and book search and have not been able to display books directly. Underthe system, students or faculty who want to read the book should make the process ofborrowing books or come directly to the library, so in terms of the efficiency of the service timeof course it is less effective. In order for the service to library users more effective, it isnecessary to Digital Library system that can accommodate the user needs to access acollection of books online. Construction of the Digital Library created first in small scale isdevoted to the Faculty of Industrial Technology UPN Veteran Yogyakarta. Digital library is builtusing web-based programming with PHP + AJAX programming language and MySQLdatabase. As for the appearance of the book pieces will be displayed in the form of animatedFlash Slideshow. System analysis method of making this application is the Data Flow Diagram(DFD) to describe the flow of data and Entity Relationship Diagram (ERD) as a depiction of therelationships between the entities table.Keyword : Digital Library, PHP, Ajax, MySQL Database, Flash Slideshow